Roles of Skeletal Muscle-Derived Exosomes in Organ Metabolic and Immunological Communication - Aoi, Wataru; Tanimura, Yuko (Frontiers in Endocrinology, 2021)
Skeletal muscles secrete various factors, such as proteins/peptides, nucleotides, and metabolites, which are referred to as myokines. Many of these factors are transported into extracellular bodily fluids in a free or protein-bound form. Furthermore, several secretory factors have been shown to be wrapped up by small vesicles, particularly exosomes, secreted into circulation, and subsequently regulate recipient cells. Thus, exosome contents can be recognized as myokines. In recipient cells, proteins, microRNAs, and metabolites in exosomes can regulate the expression and activity of target proteins associated with nutrient metabolism and immune function. The levels of circulating exosomes and their contents are altered in muscle disorders and metabolic-related states, such as metabolic dysfunction, sarcopenia, and physical fitness. Therefore, such circulating factors could mediate various interactions between skeletal muscle and other organs and may be useful as biomarkers reflecting physiological and pathological states associated with muscular function. Here, this review summarizes secretory regulation of muscle-derived exosomes. Their metabolic and immunological roles and the significance of their circulating levels are also discussed.